MELACAK TANTANGAN PERETASAN DALAM PERKEMBANGAN HUKUM DUNIA MAYA DI INDONESIA - Putra, Jay Sadikin Abdul Azis Mandala (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2024)
The digital era continues to develop, security threats, especially those related to hacking practices, have become one of the main challenges for the development of cyber law and information technology in Indonesia. Hacking, which refers to the practice of illegally entering a computer system, has raised serious concerns in efforts to keep sensitive data and information secure. This research discusses the challenges faced by Indonesia in dealing with hacking practices as part of the evolution of cyber law. This research focuses on legal changes, law enforcement efforts, and the challenges faced in law enforcement against cybercriminals. In an effort to tackle hacking practices, legislative changes, international cooperation and increasing awareness of the importance of cyber security are expected to help strengthen Indonesia's legal framework to protect its digital infrastructure. Through normative legal analysis and comprehensive qualitative analysis, this research seeks to present an overview of the efforts needed to track and overcome hacking threats in order to advance cyber law in Indonesia.